2022
DOI: 10.3389/fneur.2022.769360
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to Dementia Assessment and Diagnosis: Perspectives From Dementia Experts Within a Global Health Context

Abstract: ObjectivesDementia poses one of the greatest global health challenges, affecting 50 million people worldwide. With 10 million new cases each year, dementia is a growing burden, particularly in low- and middle-income countries (LMIC). This study aimed to identify the facilitators and barriers to providing quality dementia assessment and care in LMICs from a global health perspective.Methods/DesignA qualitative semi-structured interview study with 20 dementia expert healthcare providers from 19 countries. To be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The status of other areas related to dementia awareness, dementia risk reduction, diagnosis, treatment and care, dementia carer support, dementia information systems and research is also similar across these countries highlighting an urgent need for action. Prior reports indicate that there are barriers to dementia assessment and care – stigma about dementia, poor patient engagement, limited trained healthcare professionals who can diagnose and manage dementia, competing healthcare system priorities and insufficient funding [36]. Studies have also identified the importance of establishing research priorities to improve outcomes related to dementia [37].…”
Section: Resultsmentioning
confidence: 99%
“…The status of other areas related to dementia awareness, dementia risk reduction, diagnosis, treatment and care, dementia carer support, dementia information systems and research is also similar across these countries highlighting an urgent need for action. Prior reports indicate that there are barriers to dementia assessment and care – stigma about dementia, poor patient engagement, limited trained healthcare professionals who can diagnose and manage dementia, competing healthcare system priorities and insufficient funding [36]. Studies have also identified the importance of establishing research priorities to improve outcomes related to dementia [37].…”
Section: Resultsmentioning
confidence: 99%
“…For example, identifying, examining, and describing what “isms” are relevant to the U.S. (e.g., racism), what “isms” are unique to India (e.g., casteism) [ 43 ], what “isms” are common to the two countries (e.g., genderism/sexism), and what the crossovers or similarities between the two countries are in terms of mechanisms that drive multimorbidity would be worthwhile. For example, are there any gender-related or women-identifying disadvantage(s) due to unequal rights or pay for women in India and/or the U.S.?…”
Section: Discussionmentioning
confidence: 99%
“…Such beliefs are a key barrier to access to support services among people living with dementia and their carers. Evidence shows that stigma, accompanied by lack of awareness and knowledge, hinders the prevention, care, and treatment of people living with dementia globally (Bernstein Sideman et al, 2022). However, unlike what was found in the overall report, in which over a quarter (25.2%) of the sample thought that nothing can be done to prevent dementia (Alzheimer's Disease International, 2019), we found lower levels of agreement with such a view in each of the four groups in Brazil (less than 20%).…”
Section: Discussionmentioning
confidence: 99%